Kontribusi Industri Rumahan dalam Meningkatkan Pertumbuhan Ekonomi di Kota Watampone - Akmal Ihsan; Firdaus Firdaus (Jurnal Ilmiah Al-Tsarwah : ilmu ekonomi dan keuangan (konvensional dan syariah), 2019)
This study discusses the contribution of home industries in increasing economic growth in Watampone City. The formulation of the problem in this study is: Is the home industry contributing significantly in increasing economic growth in Watampone City. The purpose of this study is to find out whether the home industry contributes significantly in increasing economic growth in Watampone City. The results showed that, in part, the home industry contributed significantly to economic growth in Watampone City because t count t table (2.563 0.013) where the significance significance level (0,000 0.05), as well as% home industry revenue and% economic growth in the same direction (=) so that it gives a positive contribution and this shows that H0 is rejected and H1 is accepted.